Сказать жизни "Да!". Психолог в концлагере - Франкл Виктор (Альпина нон-фикшн, 2023)
Экземпляры: ф13 (20240704) / Инвентарный номер: 66799 / Цена: 510.00 / Сис.шифр: 88 / Авт.знак: Ф 83 / ГРНТИ: 15.41 / ББК: 88